2003
DOI: 10.1086/367992
|View full text |Cite
|
Sign up to set email alerts
|

Mucopurulent Cervicitis andMycoplasma genitalium

Abstract: Many cases of mucopurulent cervicitis (MPC) are idiopathic and cannot be attributed to the known cervical pathogens Neisseria gonorrhoeae, Chlamydia trachomatis, or herpes simplex virus. Because Mycoplasma genitalium is associated with nongonoccocal urethritis in men, its role in MPC, the corresponding syndrome in women, was investigated. Archived cervical specimens from women recruited in the Harborview Sexually Transmitted Disease Clinic in Seattle from 1984 to 1986 were tested, using polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
212
5
13

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(240 citation statements)
references
References 32 publications
10
212
5
13
Order By: Relevance
“…The implications for management of M. genitalium and C. trachomatis infections warrant further study into this association. While others [10] have not shown an association between these two organisms, the difference in study findings may be explained by our sample population of adolescents in whom STI infection is highly prevalent.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…The implications for management of M. genitalium and C. trachomatis infections warrant further study into this association. While others [10] have not shown an association between these two organisms, the difference in study findings may be explained by our sample population of adolescents in whom STI infection is highly prevalent.…”
Section: Discussioncontrasting
confidence: 73%
“…Point prevalence ranged from 0.8-4.1%. Previous cross-sectional studies that included some adolescents found a point prevalence between 3.5-7% [10,17,18]. The difference in point prevalence found here may be attributable to the target population for this project as the young women were not recruited from STD or family planning clinics.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Varios estudios efectuados mediante RPC han detectado M. genitalium en 15 a 25% de hombres con UNG [5][6][7][8][9] . En la mujer, M. genitalium ha sido asociado con cervicitis 5,[10][11] , enfermedad inflama-muestras clínicas fueron obtenidas con tórula fina de algodón e inmediatamente inoculadas en medio de transporte Stuart y en 1,5 ml de buffer de transporte sacarosa fosfato (buffer 2SP). Mujeres sexualmente activas: se obtuvieron dos muestras de secreción vaginal de 40 mujeres atendidas consecutivamente en el Departamento de Alto Riesgo Obstétrico (DARO) del Hospital San Juan de Dios.…”
Section: Materials Y Métodosunclassified